Security in schools: its effect on students - Phaneuf, Shannon Womer (Criminal justice: recent scholarship, 2009)
The changing school environment and the rise of security -- The research study -- Understanding the influence of school security on fear, bonding, and school climate: an overview of the literature -- Sample, measures, and procedures -- The results are in: questions answered -- Where do we go from here?: a look at the future for research, policy, and practice